Dangerous thresholds : managing escalation in the 21st century - Morgan, Forrest E. (Rand Corporation monograph series., 2008)
"Escalation is a natural tendency in any form of human competition. When such competition entails military confrontation or war, the pressure to escalate can become intense due to the potential cost of losing contests of deadly force. Cold War-era thinking about escalation focused on the dynamics of bipolar, superpower confrontation and strategies to control it. Today's security environment, however, demands that the United States be prepared for a host of escalatory threats involving not only longstanding nuclear powers, but also new, lesser nuclear powers and irregular adversaries, such as insurgent groups and terrorists. This examination of escalation dynamics and approaches to escalation management draws on historical examples from World War I to the struggle against global jihad. It reveals that, to manage the risks of escalatory chain reactions in future conflicts, military and political leaders will need to understand and dampen the mechanisms of deliberate, accidental, and inadvertent escalation. Informing the analysis are the results of two modified Delphi exercises, which focused on a potential conflict between China and the United States over Taiwan and a potential conflict between states and nonstate actors in the event of a collapse of Pakistan's government."--Jacket